Optimalisasi Konsentrasi Thidiazuron untuk Peningkatan Pertumbuhan Protocorm In Vitro Anggrek Grammatophyllum stapeliiflorum - Zozy Aneloi Noli; Naura Muthiah Arli; Suwirmen (Jurnal Penelitian Pendidikan IPA, 2024)
Cytokinins are growth regulators that play a crucial role in cell division and shoot growth. Thidiazuron, a potent cytokinin, was the focus of our research. The research aimed to determine the effect of several concentrations of Thidiazuron on the protocorm growth of Grammatophyllum stapeliiflorum and to identify the best concentration of Thidiazuron (mg/L) for the protocorm growth of G. stapeliflorum orchids in vitro. The research was conducted from January until March 2022 at the Plant Physiology Laboratory, Universitas Andalas, Padang. The research used a Completely Randomized Design (CRD) with 5 treatments and 5 replications. Several concentrations of Thidiazuron were added to MS media with various concentrations: 0 mg L-1 (A), 0.50 mg L-1 (B), 1 mg L-1  (C), 1.50 mg L-1(D), and 2 mg L-1  (E). The parameters in this research were the percentage of life explants, day of shoot appearance, number of shoots, shoot length, number of leaves, number of roots, and root length. The results showed that Thidiazuron significantly affected the protocorm growth of the G. stapeliiflorum orchid compared to the control treatment. Notably, 2 mg L-1  Thidiazuron emerged as the best concentration for all growth parameters of protocorm G. stapeliiflorum, a finding that could significantly impact our understanding of orchid cultivation and plant physiology.